2022-RA-766-ESGO Cutaneous vulvar metastasis after combined treatment of cervical cancer-case report. (20th October 2022) - Aluloski, Igor; Tanturovski, Mile; Stojcevski, Saso; Samardziski, Igor; Kostadinova-Kunovska, Slavica; Jovanovic, Rubens; Koloska, Dubravka
Abstract : Introduction/Background: Invasive adenosquamous carcinoma of the cervix has an incidence of only 4% of all epithelial cervical tumors. Additionally to the local invasion, this type of cancer is characterized by the appearance of distant metastases in the lungs, bones and liver, while cutaneous metastases are extremely rare. Methodology: We present a rare case of cutaneous vulvar metastasis originating from adenosquamous cervical cancer after combined treatment. Nine months after the operation, due to observed vulvar lesions, a clinical examination and imaging diagnostic procedures were performed. After the removal of the vulvar lesions, a histopathology report describes them as poorly differentiated adenosquamous carcinoma with identical morphological characteristics as the primary neoplasm of the cervix. Results: Cutaneous metastasis from carcinoma of the uterine cervix is very rare. The incidence of cutaneous metastases in treated cervical cancers is 0.8%, with a rare occurrence of cutaneous vulvar metastases, usually 3.5 to 6 years after surgical treatment. Therefore, this is a rare case of secondary metastatic deposit that occurs at an unusual localization for a relatively short period of time. Conclusion: Vulvar lesions in patients with previously diagnosed and treated cervical cancer need to be histologically verified in order to confirm or exclude a possible metastatic process from the primary cervical neoplasm.